2014
DOI: 10.1177/0018720814538815
|View full text |Cite
|
Sign up to set email alerts
|

Using Noninvasive Brain Stimulation to Accelerate Learning and Enhance Human Performance

Abstract: Noninvasive brain stimulation can accelerate skill acquisition in complex tasks and may provide an alternative or addition to other training methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 41 publications
0
29
0
1
Order By: Relevance
“…While pharmaceutical interventions can globally affect neural processing, an alternative physiological approach is localized brain stimulation of cortical regions associated with attention. Work into the effectiveness of brain stimulation to increase a variety of cognitive domains is currently underway . These approaches combine new knowledge regarding the neural networks that support cognition and test whether stimulation of network nodes in conjunction with cognitive training protocols can improve performance in both clinical and nonclinical populations.…”
Section: Modulating Sustained Attention Abilitymentioning
confidence: 99%
“…While pharmaceutical interventions can globally affect neural processing, an alternative physiological approach is localized brain stimulation of cortical regions associated with attention. Work into the effectiveness of brain stimulation to increase a variety of cognitive domains is currently underway . These approaches combine new knowledge regarding the neural networks that support cognition and test whether stimulation of network nodes in conjunction with cognitive training protocols can improve performance in both clinical and nonclinical populations.…”
Section: Modulating Sustained Attention Abilitymentioning
confidence: 99%
“…Recent studies demonstrated an association between excitability increase with the use of high repetitive TMS or anodal tDCS with improved motor skill learning (Butts et al, 2014;Parasuraman and McKinley, 2014;Reis and Fritsch, 2011;Reis et al, 2008Reis et al, , 2009Tanaka et al, 2011). Both dPMCs are involved in motor learning in healthy subjects and stroke patients (Stagg and Johansen-Berg, 2013;Stefan et al, 2008;Stinear et al, 2009;Wang et al, 2014;Zanon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This second phase requires longer time. The literature dealing with the effect of practice on the functional anatomy of task performance is extensive and complex, comprising a wide range of papers from disparate research perspectives (Chein and Schneider, 2005; Doyon and Benali, 2005; Parsons et al, 2005; Erickson et al, 2007; Dux et al, 2009; Wiestler and Diedrichsen, 2013; Parasuraman and McKinley, 2014; Sampaio-Baptista et al, 2014; Borghini et al, 2016). Across these studies, three main patterns of practice-related activation change can be distinguished.…”
Section: Methodsmentioning
confidence: 99%